Fruit-seed relations in Hakea: serotinous species invest more dry matter in predispersal seed protection - Groom, Philip; Lamont, Byron (1997)
The ability to maintain a canopy stored seedbank (serotiny) is characteristic of many woody genera inhabiting fire-prone environments. The relationship between level of serotiny for 94 Hakea (Proteaceae) species in southwestern Australia and follicle mass, density, three wall thicknesses and seed mass was investigated. Two species were nonserotinous (fruits open at maturity), 12 were weakly serotinous (majority of fruits open at maturity), 9 were moderately serotinous (fruits open within five years of maturity) and 71 were strongly serotinous (fruits still closed at least five years after reaching maturity). A positive relationship existed between the level of serotiny and follicle morphology. Strongly serotinous species were more likely to have heavier, woodier and thicker-walled follicles than non- and weakly serotinous species. Moderately/strongly serotinous species invested more energy (six times higher follicle:seed mass ratio) than non weakly serotinous species, consistent with increased protection of the seeds from granivores, pathogens, desiccation and/or heat. Recent work has shown that thicker fruit walls (strongly serotinous species) provide better insulation to seeds from heat, although the need to survive fire is just as critical for thin-walled, weakly serotinous species. Greater protection from granivores may provide a better explanation for the adaptive significance of dense, thick-walled serotinous follicles, as the opportunities for predispersal granivore damage are low among weakly serotinous species.